2014
DOI: 10.1144/sp401.13
|View full text |Cite
|
Sign up to set email alerts
|

Physical modelling of large-scale deformational systems in the South Polar Layered Deposits (Promethei Lingula, Mars): new geological constraints and climatic implications

Abstract: Deformation systems (DSs) locally affect the South Polar Layered Deposits (SPLDs) along the margins of the Promethei Lingula ice sheet (part of the southern Martian ice-dome). One example is the 'S 2 ' deformation system, characterized by a complex pattern of brittle and brittle-ductile structures related to kilometre-scale shear zones that deform the sequence. Moreover, soft-sediment structures affect one layer located at the base of the S 2 . An earlier structural analysis suggested that: (1) two deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The role of weak layers on the development of DSGSDs and the melting/softening of icy levels during warmer periods, hypothesized in the first works, was the subject of a subsequent quantitative study. Guallini et al [69] conducted thermal and mechanical modelling to analyze one of the previous described deformation systems. The results showed that different layers of the South Polar Layered Deposits are probably composed of CO 2 ice, which melted or deformed when surface temperatures were higher than the present.…”
Section: Planum Australementioning
confidence: 99%
See 3 more Smart Citations
“…The role of weak layers on the development of DSGSDs and the melting/softening of icy levels during warmer periods, hypothesized in the first works, was the subject of a subsequent quantitative study. Guallini et al [69] conducted thermal and mechanical modelling to analyze one of the previous described deformation systems. The results showed that different layers of the South Polar Layered Deposits are probably composed of CO 2 ice, which melted or deformed when surface temperatures were higher than the present.…”
Section: Planum Australementioning
confidence: 99%
“…Not surprisingly, landslides and mass movements also show particular concentrations in this area [2,3,5-7,10,13]. Further large-scale gravitational processes have been recognized in Acheron Dorsum [70], Noctis Labyrinthus [72], and Planum Australe [67][68][69]. The DSGSDs of Planum Australe are of particular interest, as they involve a succession mainly composed of an alternation of layers of dust and water-ice precipitates and represent the first evidence of large-scale gravity-induced deformation in the polar ice cap of a planet [68].…”
Section: Spatial Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding has important implications for graben sets on numerous worlds, including our understanding of Tharsis-radial graben, which should predate dyke emplacement, the evolution of Venusian radiating fissure systems and, supposedly, dyke-induced graben on the Moon. In a follow-on study of the Promethei Lingula ice sheet on Mars, Guallini et al (2014) integrate structural analysis with thermal and mechanical models to quantify the deformation of part of the ice sheet's South Polar Layered Deposits. They show that parts of these deposits feature soft-sediment deformation and that internal compositions are dominated by CO 2 ice.…”
Section: Physical Analogue Modelling Of Martian Dyke-induced Deformationmentioning
confidence: 99%